Social Impact of Foreign Labor Migration in Malaysia - liza, Erna; Setu, Sri Mulyati Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
In economy perception, the phenomenon of foreign labormigration in Malaysia might cause a socio-psychological impact, in this case a negative impact, on the labor's family left in the home country. Foreign labors in Malaysia, especially the male ones who are also the head of family, have changed their family's life pattern.This change disturbs their lives and, in most cases, sometimes could lead to stress andfamily problems. Human migration is a phenomenon inseparable from development process inIndonesia. It is found in many regions in Indonesia. Indonesia is an example of a country where the phenomenon of interzonal migration andinternational migration happen everytime. One of the nearest country where many Indonesian labors migrate is Malaysia.